2012
DOI: 10.7783/kjmcs.2012.20.1.027
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Ginsenosides and Color from Black Ginsengs Prepared by Steaming-Drying Cycles

Abstract: : This study was conducted to investigate changes in composition of ginsenosides and color of processed ginsengs prepared by different steaming-drying times. Processed ginsengs were prepared from white ginseng with skin by 9-time repeated steaming at 96℃ for 3 hours and followed by hot air-drying at 50℃ for 24 hours. As the times of steaming processes increased, lightness (L value) decreased and redness (a value) increased in color of ginseng powders. Crude saponin contents and ginsenosides compositions in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Nam et al. [11] reported that the ginsenoside Rb 1 , Rb 2 , Rc, Rd, Re, Rf, and Rg 1 contents decreased, and ginsenoside Rg 3 (S), Rg 3 (R), and Rk 1 contents in ginseng increased with increasing steaming times.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nam et al. [11] reported that the ginsenoside Rb 1 , Rb 2 , Rc, Rd, Re, Rf, and Rg 1 contents decreased, and ginsenoside Rg 3 (S), Rg 3 (R), and Rk 1 contents in ginseng increased with increasing steaming times.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Research studies on the effects of repeated steaming on ginsenoside composition and physicochemical properties of ginseng [10] , changes in ginsenosides from black ginseng prepared due to steam–dry cycles [11] , pH and temperature on ginsenoside composition in red ginseng water extracts [12] , high-pressure and steaming extraction on ginsenoside Rg 3 and Rh 2 contents [13] , high pressures, temperatures, and extraction solvents on ginsenosides of ginseng [14] , changes in ginsenoside composition by roasting [2] , and gamma irradiation of the conversion of ginsenoside Rb 1 to Rg 3 [15] were previously conducted. Accordingly, the primary factors that affect ginsenoside conversion include temperature, heating time, extraction solvent, and stability of ginsenosides.…”
Section: Introductionmentioning
confidence: 99%
“…Black ginseng is usually developed from fresh or white ginseng steamed several times (usually 9 times) at 96 °C for 3 h, followed by hot air-drying at 50 °C for 24 h [17,18]. While the processing method of “steaming and drying 9 times” has always been used in TCM in the processing of Radix Rehmanniae [19], this method was rarely used for the processing of ginseng in the ancient TCM.…”
Section: Preparationmentioning
confidence: 99%
“…The reductions in GS-Rd with time is less than was seen for GS-Rb1, Rb2, and Rc. This is because the decomposition of PPDs GS-Rb1, Rb2, and Rc, results in GS-Rg3 via conversion into GS–Rd [ 8 - 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nam et al [ 10 ] used six-year-old roots of the fresh ginseng and repeated the treatment of steaming for three hours at 96℃ and drying at 50℃. The method resulted in red ginseng of moisture content below 15% - 20% after drying, therefore the samples may exhibit less or uneven moisture content, that may cause differences in the rate of hydrolysis of GS compared to fresh ginseng, with moisture content of approximately 75% - 80%.…”
Section: Resultsmentioning
confidence: 99%